Free radicals and their impact on health and antioxidant defenses: a review - Nisansala Chandimali; Seon Gyeong Bak; Eun Hyun Park; Hyung-Jin Lim; Yeong-Seon Won; Eun-Kyung Kim; Sang-Ik Park; Seung Jae Lee (Cell Death Discovery)
Abstract Free radicals, characterized by the presence of unpaired electrons, are highly reactive species that play a significant role in human health. These molecules can be generated through various endogenous processes, such as mitochondrial respiration and immune cell activation, as well as exogenous sources, including radiation, pollution, and smoking. While free radicals are essential for certain physiological processes, such as cell signaling and immune defense, their overproduction can disrupt the delicate balance between oxidants and antioxidants, leading to oxidative stress. Oxidative stress results in the damage of critical biomolecules like DNA, proteins, and lipids, contributing to the pathogenesis of various diseases. Chronic conditions such as cancer, cardiovascular diseases, neurodegenerative disorders, and inflammatory diseases have been strongly associated with the harmful effects of free radicals. This review provides a comprehensive overview of the characteristics and types of free radicals, their mechanisms of formation, and biological impacts. Additionally, we explore natural compounds and extracts studied for their antioxidant properties, offering potential therapeutic avenues for managing free radical-induced damage. Future research directions are also discussed to advance our understanding and treatment of free radical-associated diseases.